2018
DOI: 10.1159/000491811
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA NEAT1 Promotes Deterioration of Hepatocellular Carcinoma Based on In Vitro Experiments, Data Mining, and RT-qPCR Analysis

Abstract: Background/Aims: Accumulated evidence indicates that lncRNA NEAT1 has important roles in various malignant tumors. In this study, we conducted a comprehensive analysis to explore the exact role of NEAT1 in hepatocellular carcinoma (HCC). Methods: The effects of NEAT1 on cell proliferation, apoptosis, migration, and invasion were measured by in vitro experiments. The expression level and clinical value of NEAT1 in HCC was evaluated based on data from The Cancer Genome Atlas (TCGA), Oncomine, and in-house real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…These include EPHA4, which has been reported to regulate the epithelial-mesenchymal transition process and promote HCC migration 25 ; the RING finger protein COP1, a p53targeting E3 ubiquitin ligase that is frequently expressed in HCC and affects HCC progression 26 ; CTNNA, a tumor suppressor in HCC 27 ; and CREB binding protein, a transcription activator that has been suggested to promote HCC by interacting with long non-coding RNA. 28 This study also identified integration sites near CNTNAP1, ZNF699, MASP1, PEX7, and the RAN binding protein 1 pseudogene, which have yet to be associated with hepatocarcinogenesis or HCC progression. Their potential association with HCC in this context warrants further investigations.…”
Section: Discussionmentioning
confidence: 70%
“…These include EPHA4, which has been reported to regulate the epithelial-mesenchymal transition process and promote HCC migration 25 ; the RING finger protein COP1, a p53targeting E3 ubiquitin ligase that is frequently expressed in HCC and affects HCC progression 26 ; CTNNA, a tumor suppressor in HCC 27 ; and CREB binding protein, a transcription activator that has been suggested to promote HCC by interacting with long non-coding RNA. 28 This study also identified integration sites near CNTNAP1, ZNF699, MASP1, PEX7, and the RAN binding protein 1 pseudogene, which have yet to be associated with hepatocarcinogenesis or HCC progression. Their potential association with HCC in this context warrants further investigations.…”
Section: Discussionmentioning
confidence: 70%
“…Previous work has shown that the lncRNAs GClnc1 and GCAWKR can serve as scaffolds for KAT2A and WDR5 in gastric cancer, and can thereby serve as positive regulators of this enzyme [5,41]. The lncRNA NEAT1 also interacts with KAT2A to promote deterioration of hepatocellular carcinoma [6]. However, the relationship of PVT1 and KAT2A has not previously been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Although intensity-modulated radiation advances in NPC treatment, tumor proliferation, and growth for NPC patients remain to be the important cause of treatment failure and cancer-related death [3,4]. Recently, an increasing body of evidence has suggested that long noncoding RNAs (lncRNAs) are involved in tumorigenesis through regulating histone modification [5,6]. However, the mechanisms that account for it remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Functional and pathway enrichment analyses were performed for DEGs using the clusterProfiler R package [25], including Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses [26]. GO terms and KEGG pathways with an adj.…”
Section: Functional and Pathway Enrichment Analysismentioning
confidence: 99%